Sophie Quire and the last Storyguard - Auxier, Jonathan (Auxier, Jonathan. Peter Nimble adventure., 2017)
When a mysterious boy arrives at her father's bookshop with his companions and a rare and mysterious book, twelve-year-old Sophie finds herself in an adventure beyond anything she has read about in her father's books.